Precipitation at the Łódź-Lublinek station during the advection of Arctic air masses - Piotrowski , Piotr (Acta Geographica Lodziensia, 2024)
To analyse the precipitation conditions at the Łódź-Lublinek station during Arctic air-mass advection (AAMA), a modified Geb method for determining Arctic air masses was used. This study examined how AAMA affects precipitation at Łódź-Lublinek station. The precipitation during AAMA is favoured by cyclonic circulation from a north-western direction. The Arctic air-mass advection from this direction is most often associated with a low-pressure system located north-east from the borders of Poland. The highest number of precipitation incidents during AAMA, in comparison to all cases, was observed from November to December and March to April, while the lowest was from May to August. The 6-hour precipitation during AAMA was lower in all months compared to precipitation that occurred under other air-masses types. This is due to the low water content in the relatively colder Arctic air masses in all seasons of the year. The low temperature of Arctic air masses also affects low precipitable water over central Europe. Among all precipitation cases related to AAMA, the lowest deviations in the precipitable water in the atmosphere and temperature were found in winter.